PERGESERAN TRADISI BELALEK DALAM BUDAYA BERTANI MASYARAKAT MELAYU SAMBAS - Wiyono, Hadi; Ramadhan, Iwan (Jurnal Studi Agama dan Masyarakat, 2021)
The purpose of this study was to analyze the shifting of Belalek tradition as seen from the factors of socio-cultural change, especially in the agricultural sector in the Sambas Malay society of Sentebang Village. The method used descriptive qualitative using observation, interview and documentation. The results revealed that people of Sentebang Village preferred to use the wage system compared to the remuneration system or called Belalek, the ease and efficiency of machine technology as a result of modernization, and the openness to changes and developments that occur. These three things have caused a shift in Belalek tradition.